2020
DOI: 10.1371/journal.pone.0229647
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of immunobiotic strains on attenuation of Salmonella induced inflammatory response in human intestinal epithelial cells

Abstract: Probiotic bacteria have the ability to modulate host immune responses and have potent therapeutic functional effects against several diseases, including inflammatory diseases. However, beneficial effects of probiotics are strain specific and their interactions with host immune cells to modulate inflammatory response are largely unknown. Intestinal epithelial cells (IECs), which are the first line of defense against invading pathogens, and connects between commensals/probiotics and immune system; therefore, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Several strains of Limosilactobacillus reduced Salmonella lipopolysaccharide (LPS)-induced gut epithelial barrier impairment by increasing tight junction protein expressions ( Fang et al, 2010 ; Yeung et al, 2013 ). Limosilactobacillus probiotics attenuated Salmonella -induced gut inflammation by reducing pro-inflammatory cytokine production by the attenuation of TLRs activation in vitro ( Kanmani and Kim, 2020 ). Kanmani and Kim (2020) showed that Limosilactobacillus isolated from Korean food increased production of the immunosuppressive cytokine IL-10, transforming growth factor (TGF)-β, and antimicrobial peptide β-defensin by manipulating the expression of TLR negative regulators in human colonocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strains of Limosilactobacillus reduced Salmonella lipopolysaccharide (LPS)-induced gut epithelial barrier impairment by increasing tight junction protein expressions ( Fang et al, 2010 ; Yeung et al, 2013 ). Limosilactobacillus probiotics attenuated Salmonella -induced gut inflammation by reducing pro-inflammatory cytokine production by the attenuation of TLRs activation in vitro ( Kanmani and Kim, 2020 ). Kanmani and Kim (2020) showed that Limosilactobacillus isolated from Korean food increased production of the immunosuppressive cytokine IL-10, transforming growth factor (TGF)-β, and antimicrobial peptide β-defensin by manipulating the expression of TLR negative regulators in human colonocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Limosilactobacillus probiotics attenuated Salmonellainduced gut inflammation by reducing pro-inflammatory cytokine production by the attenuation of TLRs activation in vitro (Kanmani and Kim, 2020). Kanmani and Kim (2020) showed that Limosilactobacillus isolated from Korean food increased production of the immunosuppressive cytokine IL-10, transforming growth factor (TGF)-β, and antimicrobial peptide β-defensin by manipulating the expression of TLR negative regulators in human colonocytes. Liu et al (2019) demonstrated anti-Salmonella activity of Limosilactobacillus in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of TLR signaling might represent an additional mechanism through which probiotics exert their effects in rheumatic diseases. Besides their ability in binding specific TLRs and affect downstream signaling, it has been shown that some lactobacillus strains can promote the expression of proteins which negatively regulate TLR activity, thus attenuating the inflammatory response induced by different pathogens (41).…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…Probiotics can activate the gut immune system by direct interaction with the intestinal epithelial and immune cells and modulate lamina propria and extraintestinal immune cell functions (8)(9)(10). In addition, one of the most extensively effects documented for certain probiotic strains are their capacity to exclude or inhibit enteric pathogens such as Salmonella (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%